PENGARUH SiLPA DAN EFEKTIVITAS KEUANGAN DAERAH TERHADAP BELANJA DAERAH DENGAN PERTUMBUHAN EKONOMI SEBAGAI PEMODERASI - Nanik Murtiningsih (2017)
This research was conducted to examine the effect of SiLPA, regional financial effectiveness on capital expenditures to economic growth as the moderating variable. The research objects are provinces in Indonesia. Total population are 33 province for year of 2010 until 2014. The sampling technique is purposive sampling method which results for 29 province with 145 sample. Data obtained from the budget realization report that published by the Ministry of Finance. The analysis technique used in this research is multiple linear regression, with tested by the classical assumption first. The result by using 5% alpha level to the formed hypothesis is SiLPA had not significant influence on capital expenditures while regional financial effectiveness and economic growth significantly influence capital expenditures. Moderating variable (economic growth) had a capable for moderating the effect of regional financial effectiveness on capital expenditure, but not able to moderate the influence of variable SiLPA on capital expenditure.